Seismic shifts in economic theory and policy: From the Bernanke Doctrine to Modern Money Theory - Pavlina R. Tcherneva; Éric Tymoigne (Levy Economics Institute of Bard College, 2024)
This paper evaluates the relationship between monetary and fiscal policy and the relative effectiveness of macroeconomic stabilization through the lens of Modern Money Theory (MMT). We articulate previously-neglected aspects of monetary sovereignty to offer a new interpretation of the Bernanke Doctrine that emerged in the wake of the 2008 Global Financial crisis. This Doctrine validated key MMT precepts and paved the way for fiscal policy activism in response to COVID19. The paper argues that fiscal and monetary policy coordination is not new or rare. It is an intrinsic feature of sovereign monetary regimes, allowing for more effective policy responses to financial crises or pandemics. To the extent that monetary policy is able to stabilize an unstable economy, it is largely due to its fiscal components. This recognition also calls for a rethinking of fiscal policy.
Keywords: E12; E58; E61; H62; H63; 330; Modern Money Theory; MMT; Bernanke; Great Financial Crisis; history of money; monetary systems; monetary sovereignty; tax-driven money; consolidated government; government debt and deficit; quantitative easing; fiscal components of monetary policy; nonstandard Open Market Operations; COVID fiscal relief